Primary percutaneous stenting above the ampulla versus endoscopic drainage for unresectable malignant hilar biliary obstruction (TESLA RCT): study protocol for a multicenter randomized controlled trial - M. Rousian; V. van Verschuer; S. Franssen; D. Bijdevaate; R. P.H. Bokkers; A. E. Braat; J. de Bruijne; M. J. Bruno; M. C. Burgmans; O. M. van Delden; M. Dewulf; J. I. Erdmann; et al. (BMC Cancer)
Abstract Background Patients with malignant hilar biliary obstruction typically present with painless jaundice. They commonly have perihilar cholangiocarcinoma (pCCA), but also intrahepatic cholangiocarcinoma, gallbladder cancer, and metastases to the liver hilum can present with hilar biliary obstruction. Endoscopic biliary drainage is the standard of care in most centers. Many patients develop drainage-related complications after endoscopic biliary drainage for malignant hilar biliary obstruction, in particular cholangitis, resulting in reinterventions, clinical deterioration and a high mortality rate. Primary percutaneous stenting (PPS) aims to avoid bacterial contamination and reduce drainage-related complications. The aim of this randomized controlled trial is to compare PPS with endoscopic biliary drainage in patients with unresectable malignant hilar biliary obstruction. Methods This multicenter phase 3 randomized controlled trial (TESLA RCT) will recruit 148 patients with unresectable malignant hilar biliary obstruction in six Dutch tertiary academic referral centers. Diagnosis of malignant hilar biliary obstruction is pathologically confirmed or determined as very likely by the multidisciplinary team. In the intervention arm, patients undergo primary percutaneous stenting with uncovered self-expandable metal stents without crossing the ampulla and without leaving an external drain. In the control arm patients undergo endoscopic biliary drainage according to international guidelines. The primary endpoint is major complications within 90 days after randomization. Secondary outcomes include technical success, reintervention rates, decrease of bilirubin levels, eligibility for palliative systemic treatment, quality of life, and overall survival. Discussion The multicenter TESLA RCT compares primary percutaneous stenting with endoscopic biliary drainage in patients with unresectable malignant hilar biliary obstruction. First patient was randomized on August 9, 2023. Trial registration Netherlands Trial Register (NL-OMON53463), registered on May 12, 2023, and Clinicaltrials.gov (NCT06671418), registered on November 1, 2024.